The work stress, occupational burnout, coping strategies and organizational support of elite sports coaches in Sichuan Province: the mediating role of organizational support - Yu, Liang; Cheng, Liang (Frontiers in Psychology, 2024)
Objective This study investigated the relationships between job pressure, occupational burnout, organizational support and coping strategies among competitive sports coaches in Sichuan Province, China. It also assesses the impact of job pressure on occupational burnout and the mediating roles of organizational support and coping strategies. Methods A survey was conducted with 207 competitive sports coaches from Sichuan Province, China. Basic information and data on job pressure, occupational burnout, organizational support and coping strategies were collected. Correlations between variables were analyzed, and a theoretical model for hypothesizing the mediating effects was established. A multiple regression model was used to predict the relationships between occupational burnout and job pressure, organizational support and coping strategies. Results (1) Job pressure was significantly positively correlated with occupational burnout (R = 0.436, p < 0.001) and negative coping (R = 0.389, p < 0.001) but significantly negatively correlated with organizational support (R = −0.503, p < 0.001). Occupational burnout was significantly negatively correlated with academic title (R = −0.158, p = 0.023) and organizational support (R = −0.349, p < 0.001) but significantly positively correlated with negative coping (R = 0.440, p < 0.001). Organisational support was significantly positively correlated with positive coping (R = 0.222, p = 0.001) but significantly negatively correlated with negative coping (R = −0.207, p = 0.003). (2) Mediating effects: Job pressure indirectly affects occupational burnout via organizational support and negative coping strategies. (3) Multiple regression: Y1 (Job Pressure) = 69.262 + 1.172 × Emotional Exhaustion −2.231 × Emotional Support +1.041 × Negative Coping −6.554 × Academic Title (from high to low). Y2 (Occupational Burnout) = 25.609 + 0.141 × Job Pressure − 0.306 × Organisational Support +0.620 × Negative Coping −2.097 × Academic Title. Conclusion Job pressure is a significant factor leading to occupational burnout among competitive sports coaches in Sichuan Province, China, and factors such as role, interpersonal relationships and career development are closely related to occupational burnout. The sense of organizational support and negative coping strategies play a mediating role between job pressure and occupational burnout. Reducing emotional exhaustion and negative coping, enhancing emotional support and improving the academic titles of coaches can help to reduce job pressure and occupational burnout among competitive sports coaches in Sichuan Province.